Rectangular core-collapse supernova remnants: application to Puppis A. Issue 1 (4th July 2022) - Meyer, D M-A; Velázquez, P F; Petruk, O; Chiotellis, A; Pohl, M; Camps-Fariña, A; Petrov, M; Reynoso, E M; Toledo-Roy, J C; Schneiter, E M; Castellanos-Ramírez, A; Esquivel, A
ABSTRACT: Core-collapse supernova remnants are the gaseous nebulae of galactic interstellar media (ISM) formed after the explosive death of massive stars. Their morphology and emission properties depend both on the surrounding circumstellar structure shaped by the stellar wind–ISM interaction of the progenitor star and on the local conditions of the ambient medium. In the warm phase of the Galactic plane (n≈ 1 cm^-3, T≈ 8000 K ), an organized magnetic field of strength 7 μ G has profound consequences on the morphology of the wind bubble of massive stars at rest. In this paper, we show through 2.5D magnetohydrodynamical simulations, in the context of a Wolf–Rayet-evolving 35 M_ star, that it affects the development of its supernova remnant. When the supernova remnant reaches its middle age (15\!-\!20 kyr ), it adopts a tubular shape that results from the interaction between the isotropic supernova ejecta and the anisotropic, magnetized, shocked stellar progenitor bubble into which the supernova blast wave expands. Our calculations for non-thermal emission, i.e. radio synchrotron and inverse-Compton radiation, reveal that such supernova remnants can, due to projection effects, appear as rectangular objects in certain cases. This mechanism for shaping a supernova remnant is similar to the bipolar and elliptical planetary nebula production by wind–wind interaction in the low-mass regime of stellar evolution. If such a rectangular core-collapse supernova remnant is created, the progenitor star must not have been a runaway star. We propose that such a mechanism is at work in the shaping of the asymmetric core-collapse supernova remnant Puppis A.